COVID-19-related music-video-watching among the Vietnamese population: lessons on health education - Nguyen Tuan Hung; Vu Thu Trang; Trinh Van Tung; Nguyen Xuan Long; Ha Thi Thu; Tran Song Giang; Tran Hoang Thi Diem Ngoc; Vu Thi Thanh Mai; Nguyen Kim Oanh; Nguyen Thi Phuong; Nguyen Hang Nguyet Van; Nguyen Hanh Dung; et al. (AIMS Press, 2021)
Background: Health education through music video plays a vital role in raising a person's knowledge, attitudes, and behaviors positively connected to health during COVID-19 pandemic. Objective: This study aimed to estimate the prevalence of COVID-19-related music-video-watching and examine associated factors among the Vietnamese population. Methods: A cross-sectional study in Vietnam was conducted in February 2021 via the Internet. Results: Among 658 participants, the prevalence of COVID-19-related music-video-watching was 89.1% among people. In the multivariable regression models, significant factors for COVID-19-related music-video-watching were living area, types of housemate, age groups, and current occupation. Conclusions: Lessons on health education to fight against the COVID-19 pandemic in Vietnam could be useful for similar settings in the world.